Estruturas híbridas de poliamida 6-madeira (eucalyptus grandis) sobremoldadas por injeção - Zanchetta, Giovana Zanetini (Universidade Federal de São Carlos, 2026)
Polymer–wood hybrid (PWH) structures represent a promising alternative for sustainable structural applications. This study introduces the development of hybrid joints composed of polyamide 6 (PA6) and Eucalyptus grandis wood produced by injection overmolding, without the use of adhesives or chemical surface treatments. Two scarf joint geometries with single and double chamfers at 45° were designed and evaluated in terms of mechanical performance and interfacial adhesion mechanisms. Shear strength was determined through quasi-static mechanical tests, while the interface was characterized by scanning electron microscopy (SEM) and X‑ray microtomography (µCT). Microstructural analyses revealed a well‑defined interface, with PA6 penetrating wood vessels and forming polymer protrusions (~50 µm) that promote mechanical interlocking. Mechanical tests showed good repeatability, with hybrid joints reaching shear strength values of up to 8.1 ± 0.6 MPa, comparable to those reported in the literature for polymer–wood hybrid lap joints. Complementary digital image correlation (DIC) analyses indicated efficient mechanical coupling between the components, with a more homogeneous strain distribution for the single‑chamfer configuration, suggesting more effective stress transfer under mechanical loading.
Injection-overmolded polyamide 6–wood (eucalyptus grandis) hybrid structures
Keywords: Adesão direta; Junta híbrida; Sobremoldagem por injeção; Madeira; Direct adhesion; Hybrid joint; Injection overmolding; Wood; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 9. Indústria, Inovação e Infraestrutura